Professionalism and Competence of Nadzir Waqf in Pondok Modern Darussalam Gontor - Amal, Muhammad Ikhlasul Amal; Rusli, Lathiefa; Firmansyah, Yayan (Islamic Business and Management Journal, 2024)
The success of waqf management lies in the existence of nadzir in maximizing the role of waqf, if waqf is managed professionally and competently it will become a potential Islamic institution and can carry out its functions, its progress, and the decline of waqf can also be seen from the good or bad management of waqf. Pondok Modern Darussalam Gontor is a waqf Islamic institution since 1958 which is engaged in education. The existence of waqf in Gontor has been proven until now. All of that cannot be separated from the important role of the waqf nadzir who manages waqf assets properly and correctly. This research uses qualitative methods by guiding researchers to explore and portray thoroughly and deeply. The results of this study indicate that the professionalism and competence of the waqf nadzir at Pondok Modern Darussalam Gontor has been running. Understanding of the cottage, five souls and five terms, supervision, and regeneration are the implementation of the professionalism of the waqf nadzir at Pondok Modern Darussalam Gontor. Training and preparation of SOPs are the implementation of waqf nadzir competence at Pondok Modern Darussalam Gontor. according to the nature of education and teaching in Pondok Modern Darussalam Gontor. Five terms and five souls are the basis used by waqf nadzirs to manage and produce waqf assets owned by Pondok Modern Darussalam Gontor. The provision of training and seminars every year and practice afterwards make the competence of waqf nadzirs at Pondok Modern Darussalam Gontor increase